Instructor's Guide to Accompany Blueprint reading and drafting for plumbers - Michael A. Joyce (Delmar/Thomson Learning, 2004)
Proper interpretation of print drawings requires an individual to possess fundamental knowledge of drafting techniques. This book fosters an understanding of the complex process of accurately creating and reading shop drawings and blueprints; a vital component for increasing productivity and minimizing costly installation errors. Emphasis is given to the importance of project documents, design intent, and material organization necessary for creating print drawings that can expedite installations on the job. Code data, sizing criteria, and mathematics coverage help enhance the communication process between a designer and installer. With a focus on the manual drafting skills that cannot be replaced by computer software, this book fills a void in the plumbing industry created by the technological advancement of CAD